APEC 2000. Fifteenth Annual IEEE Applied Power Electronics Conference and Exposition (Cat. No.00CH37058)
DOI: 10.1109/apec.2000.822606
|View full text |Cite
|
Sign up to set email alerts
|

Application of power electronics to the distribution transformer

Abstract: This paper describes the design and prototype construction of a novel Solid State Transformer. Replacing distribution transformers with solid state devices provides control over the waveshapes and output voltage and can therefore mitigate many power quality problems. A 10kVA prototype was constructed to transform 7200V single phase to 240/120V and has been tested to one-half design voltage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…The so-called power characteristics include the amplitude, phase, frequency and waveform of the voltage and current [9], [10].…”
Section: Energy Routermentioning
confidence: 99%
“…The so-called power characteristics include the amplitude, phase, frequency and waveform of the voltage and current [9], [10].…”
Section: Energy Routermentioning
confidence: 99%
“…It is envisioned that a solid state transformer or some other kind of electronically controlled transformer shall be commercialized (e.g., [16,17]). …”
Section: Distribution Transformer Designsmentioning
confidence: 99%
“…Electronic power transformer (EPT) is a new intelligent power transformer enhancing the functions of the conventional power transformer and achieving the flexible ac transmission systems (FACTS) by power electronic conversion and has attracted much attention from both academy and industry [1][2][3][4][5]. Most of the studies reported recently concentrated on its main circuit topology design, power quality improvement for customers, parallel operating control technology and mathematical model establishing [6][7][8][9] and the prototypes applied in the distribution system have been implemented [1,4].…”
Section: Introductionmentioning
confidence: 99%